Sexual Dysfunction Induced by Antidepressants—A Pharmacovigilance Study Using Data from VigiBaseTM - Rene Zeiss; Kathrin Malejko; Bernhard Connemann; Maximilian Gahr; Verena Durner; Heiko Graf (Pharmaceuticals, 2024)
Sexual dysfunction is a common side effect of antidepressants, significantly impacting patients’ quality of life and treatment adherence. This study investigates the relationship between sexual dysfunction and antidepressants by analyzing data from VigiBase™, the World Health Organization’s global database of individual case safety reports. In this study, we examined, for the first time, reports related to sexual response—desire, arousal, and orgasm—by grouping appropriate side effect terms and calculated the reporting odds ratios (RORs) for various antidepressants. The findings of this study highlight a high disproportional reporting of sexual dysfunction, particularly with selective serotonin reuptake inhibitors and serotonin–norepinephrine reuptake inhibitors. In contrast, agents such as agomelatine, bupropion, and mirtazapine showed a lower association. Furthermore, we investigated the correlation between reporting odds ratios and the binding affinities of antidepressants to specific neurotransmitter receptors and transporters, unveiling significant relationships that provide insights into the pharmacodynamic pathways underlying these adverse effects. For instance, a positive correlation was observed between the serotonin transporter and side effects in the category desire: r (19) = 0.67, p = 0.001 These insights underscore the necessity for clinicians to consider sexual side effects when prescribing antidepressants and to monitor and address these issues to improve patient outcomes.